Wariness, an adaptive trait for survival in Krefft’s puddle frog (Phrynobatrachus krefftii) (2015)
Wariness has been defined as the trait of being cautious and watchful. It is the condition of being alert and careful forethought to avoid harm or risk. The distance at which an animal will initiate flight in relation to the position of the predator, as well as the final distance that it places between itself and the predator when it stops running, has been used as an index of its degree of wariness. An understanding of the adaptive behavior of an animal will help its conservation and management. Krefft’s puddle frog (Phrynobatrachus krefftii) is vulnerable and it is endemic to the East Usambara mountains, Tanzania. It is over all a cryptic species. However, males use visual signaling in intra-specific communication by exposing their bright yellow vocal sacs, a trait which is believed they evolve because of their noisy streamside habitat. Being conspicuous may as well pose danger to these animals as they are prone to be easily recognized and preyed upon. Therefore it is expected that wariness can be one of the compensating traits for conspicuousness in Krefft’s Puddle Frogs. Comparisons were made between three groups of individuals: yellow throated males, yellowish-throated females and white-throated females. A second comparison was made between males with differences in throat brightness. In both comparisons wariness was investigated. The results indicate that males which are more conspicuous significantly showed higher wariness than the less conspicuous males. Also, slight differences were found in wariness between the three groups of individuals (but these results were not in all cases significant).It can then be concluded that P. krefftii have evolved wariness as one of the strategies to avoid predation alongside with its evolution of its bright yellow throat colouration.